2004
DOI: 10.1042/bj20031974
|View full text |Cite
|
Sign up to set email alerts
|

The shed ectodomain of type XIII collagen affects cell behaviour in a matrix-dependent manner

Abstract: Transmembrane type XIII collagen resides in adhesive structures of cells and tissues, and has therefore been implicated in cell adhesion and in adhesion-dependent cell functions. This collagen also exists as a soluble protein in the pericellular matrix, as the ectodomain is released from the plasma membrane by proteolytic cleavage. Analysis with various protease inhibitors led to confirmation of the furin family of proprotein convertases as the protease group responsible for the shedding of the ectodomain, cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 48 publications
(88 reference statements)
4
47
0
1
Order By: Relevance
“…To get an idea whether other PCs are able to compensate for furin activity, LoVo cells, which are known to lack furin but still contain active PACE4 and PC7 (4,25,26), were employed. Upon transfection with full-length ␣1(XXIII) cDNA, they showed strongly reduced shedding of collagen XXIII compared with other transfected cell lines (supplemental Fig.…”
Section: Furin/proprotein Convertases Are the Major Class Of Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…To get an idea whether other PCs are able to compensate for furin activity, LoVo cells, which are known to lack furin but still contain active PACE4 and PC7 (4,25,26), were employed. Upon transfection with full-length ␣1(XXIII) cDNA, they showed strongly reduced shedding of collagen XXIII compared with other transfected cell lines (supplemental Fig.…”
Section: Furin/proprotein Convertases Are the Major Class Of Enzymesmentioning
confidence: 99%
“…Whereas collagen XVII is more distantly related, types XIII, XVII, XXIII, and XXV all exist in two forms: a transmembrane form and a shed ectodomain form. Whereas collagen XVII is shed from the surface by TACE (tumor necrosis factor-␣-converting enzyme), a member of the ADAM (a disintegrin and metalloproteinase) family (2), mutation analysis of collagens XIII and XXV demonstrated that the protease furin produces the shed forms (3,4). Initial cell culture studies suggested an involvement of furin either directly or indirectly in the cleavage of collagen XXIII as well (5).…”
mentioning
confidence: 99%
“…They are also implicated in the ectodomain shedding of some substrates such as type XIII collagen [43]. The involvement of proprotein convertases in ectodomain shedding could be either through direct cleavage of the substrate, or indirect activation of ADAMs and MMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, ectodomain in cell extracts is derived from gliomedin molecules still anchored in the cell membrane because one or two of the three chains remains uncleaved by furin. Pulse-chase experiments on cells expressing membrane-bound gliomedin revealed rapid shedding of the protein from cell surfaces as shown for collagens XVII and XIII (3,41).…”
Section: Discussionmentioning
confidence: 99%